Wind power converters improving the power system stability - Leon, Enrique Andres (2016)
This study analyses the coordinated actions of modern wind power plants for improving the transient and small-signal stability in power systems. Supplementary controls on wind farms are considered, and specific modifications on the controllers are tailored to increase the grid-support services. The proposal is analysed and validated in a practical power system based on the Argentine electrical network. The wind farm supplementary controls use active and reactive power control loops as well as local and remote measurements. Local controls can rapidly respond decelerating the system frequency in the first instants of a fault, consequently reducing the transient angle separations and improving the first-swing stability. On the other hand, remote controls using global information are able to increase the damping of low-frequency inter-area oscillations. Structures combining centralised and decentralised control approaches will become more common in the near future. With this aim, the integration of fast local controls with remote controls is thoroughly studied using non-linear time-domain simulations and eigenvalue analyses. A robustness evaluation is also performed to validate the proposal over a wide range of operating conditions.